STUDI ALGORITMA BABELRTS UNTUK PELAKSANAAN REGRESSION TEST SELECTION (RST) - Rahmani, Ani (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Software testing (testing) is a crucial stage in software development. The success of the testing process will ensure the quality of the software. In the regression testing process, one issue is that not all test cases (retest all) in the test suite need to be executed. Retest all will consume massive resources, as well as a long time. Regression testing techniques seek to find ways to reduce test execution time. One of the regression testing techniques is test case selection, also known as regression test selection (RTS). This paper describes a study on babelRTS, an RTS algorithm, to see its effectiveness. Effectiveness is measured by comparing the execution time of the execution retest all and babelRTS. Experiments were carried out on five software under tests (SUT) that had some faults. Test cases are prepared by designing for each SUT. The results showed a reduction in time so that the effectiveness reached a maximum of 32%, and average of 23% .